ON A CLASS OF RICCI-FLAT DOUGLAS METRICS - Sevim, Esra Sengelen; Shen, Zhongmin; Zhao, Lili (World Scientific Publ Co Pte Ltd, 2012)
In this paper, we study a special class of Finsler metrics which are defined by a Riemannian metric and a 1-form on a manifold. We find equations that characterize Ricci-flat Douglas metrics among this class.
Keywords: (Alpha, Beta)-Metrics; Douglas-Metric; Ricci Curvature